SoloVerse: Strategi Gamifikasi Pariwisata Interaktif untuk Meningkatkan Daya Saing Pariwisata di “Kutha Sepisan Sing Tak Eling Pas Pengen Dolan” - Eusebius Vercelli Ananda Satya Ardany; Amelia Putri; Henrichus Bramastya Chandra Nugraha; Adhi Setya Hutama; Bondan Wiratmoko Budi Santoso; Gregorius Adi Prastiantomo (Badan Riset dan Inovasi Daerah Kota Surakarta, 2025)
Tourism plays a key role in the economic development and cultural preservation of Surakarta City, yet it remains underdeveloped compared to Yogyakarta, despite their similar geographical and cultural characteristics. In 2024, the number of tourists visiting Surakarta was less than half that of Yogyakarta. To boost Surakarta's tourism, an innovative strategy is required to attract more visitors and foster repeat tourism. This study employs a mixed-method approach, analyzing literature sources using descriptive, comparative, and projective techniques. It examines the factors contributing to Surakarta's low tourist numbers, analyzes the success of Pokémon GO, and formulates SoloVerse, an augmented reality mobile game. Key factors influencing tourism include Surakarta's uniqueness, beauty, cultural diversity, and available attractions. The success of Pokémon GO is attributed to six critical factors: progressiveness, contextual engagement, app positivity, game mechanics, user interest, and expectations. SoloVerse, which integrates these factors, is a location-based game that combines entertainment with educational content about Surakarta's local culture. It is projected to attract 1.3 million users and potential tourists, contributing to Surakarta's regional economic growth. This study offers a strategic recommendation for the Surakarta City Government to enhance tourism competitiveness and serves as a basis for future research on augmented reality games.